DOMESTIC VIOLENCE AS SOCIAL DEGENERATION, CAUSES, EFFECTS, CONSEQUENCES - Narcis Dumitru BADEA (Challenges of the Knowledge Society)
Domestic violence cannot be put into a definition, as it has a multitude of manifestations determined by, mentalities, history, religious upbringing, punitive legislation, education, etc, with geographical and historical variability. Updated studies show that domestic violence can have adverse consequences for family life and for social and economic life as a whole. The causes of domestic violence range from problems of upbringing, mentality, traditions, economic-financial situation, vices, to negative effects in the workplace and the costs incurred by the authorities in protecting the abused. In addition to legislation and education, religious factors play an important role in influencing local customs. From a historical point of view, it can be said that it is only since the 20th century that the issue of equal rights between women and men, including women's right to vote and the protection of minors, has been raised, but not all states have understood to implement them, with different justifications. Of course, there have also been strong, more or less minority, even reactionary resistance to maintaining the traditionalist rights of men over family members, so that beyond the many meanings associated with it, violence is an abuse of power, almost always linked to a position of power and the imposition of that power on others. This characterisation best defines the situation of the man in relation to that of the woman, child or elderly person within the family unit. The development of the economy locally and globally has contributed to an increased need for additional labour, so that the manufacturing industries have differentiated in favour of men and women. In "civilised" countries with functioning democracies, the state is involved both in the establishment of legislation against discrimination of any kind and in the protection of abused persons of both sexes and minors, and budgetary funds are even provided.